Asthma in Pregnancy: Mechanism and Clinical Implication - Triya Damayanti; Sri Pudyastuti (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2020)
Asthma in pregnancy can influence clinical status of an asthma patient. Study showed that one third of asthma patients were worsening, one third stable and one third improving. During pregnancy, lung function, ventilation pattern and gas diffusion are influenced by biochemistry (hormonal) and mechanic. Mechanism in pregnancy with asthma including hypoxia, inflammation, corticosteroids therapy, history of exacerbation, smoking mother and changes in placenta function. Hormonal status during pregnancy is different with non-pregnancy woman which hormonal level changes through the pregnancy time. Those changes can influence lung function in pregnancy. Treatment of asthma in pregnancy is giving optimal asthma therapy, therefore it can improve asthma control, also the quality of life of a mother and her fetus during pregnancy.